1999
DOI: 10.1074/jbc.274.28.19778
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biosynthesis of Iron-Molybdenum Cofactor and Maturation of the nif-encoded Apodinitrogenase

Abstract: NifH has three different roles in the nitrogenase enzyme system. Apart from serving as the physiological electron donor to dinitrogenase, NifH is involved in iron-molybdenum cofactor (FeMo-co) biosynthesis and in maturation of the FeMo-co-deficient form of apodinitrogenase to a FeMo-co-activable form (apodinitrogenase maturation). The exact roles of NifH in these processes are not well understood. In the present study, the features of NifH required for the aforementioned processes have been investigated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…Individual alignments showed that, over this stretch, ApbC was 40% identical and 58% similar to MinD from Clostridium acetobutylicum, 20% identical and 34% similar to NifH from Methanococcus voltae, and 17% identical and 29% similar to CooC from Rhodospirillum rubrum. Proteins in each of these families have demonstrated ATPase activity (19,25,44). The first 115 amino acids of ApbC showed no significant homology with other proteins and contained no defined protein motifs.…”
Section: Resultsmentioning
confidence: 99%
“…Individual alignments showed that, over this stretch, ApbC was 40% identical and 58% similar to MinD from Clostridium acetobutylicum, 20% identical and 34% similar to NifH from Methanococcus voltae, and 17% identical and 29% similar to CooC from Rhodospirillum rubrum. Proteins in each of these families have demonstrated ATPase activity (19,25,44). The first 115 amino acids of ApbC showed no significant homology with other proteins and contained no defined protein motifs.…”
Section: Resultsmentioning
confidence: 99%
“…Biosynthesis and maturation of the nickel enzymes urease, CO-dehydrogenase, and [NiFe] hydrogenase, as well as the FeMo cofactor of nitrogenase, involve nucleotide-dependent steps mediated by a specific nucleotide-binding protein (25,26,31,41). The nucleotide-dependent steps in the maturation of [NiFe] hydrogenases involve GTP hydrolysis coupled to nickel donation (31) and ATP hydrolysis coupled to the synthesis of CN ligands to iron (9).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments correlate ATP hydrolysis by NifH to molybdenum incorporation into the FeMo-co precursor (38). However, NifH mutant variants that bind but do not hydrolyze Mg · ATP were functional in FeMo-co synthesis in vitro (60) and in vivo (24). Whether the electron transfer ability of NifH is required for this role is also at disagreement.…”
Section: Role Of Nifen and Its Association With Nifhmentioning
confidence: 99%